2013
DOI: 10.1109/tits.2012.2206387
|View full text |Cite
|
Sign up to set email alerts
|

VIP-WAVE: On the Feasibility of IP Communications in 802.11p Vehicular Networks

Abstract: Vehicular communication networks, such as the 802.11p and Wireless Access in Vehicular Environments (WAVE) technologies, are becoming a fundamental platform for providing real-time access to safety and entertainment information. In particular, infotainment applications and, consequently, IP-based communications, are key to leverage market penetration and deployment costs of the 802.11p/WAVE network. However, the operation and performance of IP in 802.11p/WAVE are still unclear as the WAVE standard guidelines f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…Range Extending Vehicles (REV) play the role of relays towards the infrastructure or IVs; eventually, a Leaf Vehicle (LV) at the end of the chain would have access to the infrastructure. This is a generalization of the pattern proposed in the VANET literature through different terms, relaying being more frequent [8] [19] [22] [14].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Range Extending Vehicles (REV) play the role of relays towards the infrastructure or IVs; eventually, a Leaf Vehicle (LV) at the end of the chain would have access to the infrastructure. This is a generalization of the pattern proposed in the VANET literature through different terms, relaying being more frequent [8] [19] [22] [14].…”
Section: Introductionmentioning
confidence: 92%
“…To that end, the protocol stacks proposed by standardization bodies (IEEE, ETSI, ISO) include mandatory IPv6 support. From a networking standpoint, the connectivity problem of end-to-end IP-based applications is usually addressed by the use of Mobile IPv6 with NEtwork MObility extension (MIPv6/NEMO), in particular for V2I communications [8].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the front MR can perform the pre-handoff procedure to reduce the handoff delay of the rear MR. A similar scheme also was introduced in [34], in which vehicles are grouped into clusters and the cluster head is selected as an MR to maintain the IP mobility for other vehicles. Different from the aforementioned schemes, which are based on a generic IEEE 802.11 network for V2I, a recent study in [36] proposed a Vehicular IP in WAVE (VIP-WAVE) framework that defines the IP configuration for extended and non-extended IP services, and a mobility management scheme supported by Proxy Mobile IPv6 over WAVE. With this framework, it has been shown that the QoS of WAVE/IEEE 802.11p can also be improved by the signaling and movement detection mechanisms.…”
Section: ) Vanet Protocolsmentioning
confidence: 99%
“…deployed along roadsides). The combination of intelligent transportation systems and vehicular networking presents a variety of new services such as: a) improvement of passenger and road safety [1], b) traffic management [2], c) monitoring and road surveillance [3], d ) hot-spot guidance [4], e) on-thefly broadband Internet access [5], f ) remote region connectivity [6], g) information sharing and dissemination [7], h) peer-to-peer services [8], and so forth.…”
Section: Overviewmentioning
confidence: 99%